Painful Foot Disorders in the Geriatric Population: A Narrative Review. (September 2019) - Oh-Park, Mooyeon; Kirschner, Jonathan; Abdelshahed, Dena; Kim, Dennis D.J.
Abstract : Abstract: Painful foot disorders are highly prevalent among older adults causing a significant impact on mobility, function, and risk of falls. Despite its significance, foot pain is often interpreted as a normal part of aging and relatively ignored by health care providers as well as by the older people themselves. Accurate diagnosis of the cause of foot pain is possible for most cases via clinical evaluation without a costly workup. Clinicians should consider, not only musculoskeletal pathologies but also vascular and neurological disorders in older patients with foot pain. Fortunately, most patients improve with physiatric, nonoperative interventions involving biomechanical analysis, function-oriented rehabilitation programs and therapeutic exercise, the use of proper footwear and orthoses, and selected percutaneous interventions, as indicated. In this review, we discuss the physiologic changes of the aging foot relevant to foot pain, the impact of painful foot disorders on function and other key outcomes, and principles of diagnosis and intervention. We also briefly describe painful foot disorders of the older people commonly encountered in a physiatric practice.